2004
DOI: 10.1002/prot.20203
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray structure of a membrane‐bound β‐glycosidase from the hyperthermophilic archaeon Pyrococcus horikoshii

Abstract: The beta-glycosidase of the hyperthermophilic Archaeon Pyrococcus horikoshii is a membrane-bound enzyme with the preferred substrate of alkyl-beta-glycosides. In this study, the unusual structural features that confer the extreme thermostability and substrate preferences of this enzyme were investigated by X-ray crystallography and docking simulation. The enzyme was crystallized in the presence of a neutral surfactant, and the crystal structure was solved by the molecular replacement method and refined at 2.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…The presence of a cluster of positively charged residues in the catalytic domain of the chitinase B from Serratia marcescens was reported by van Aalten et al 27 Similarly, some other glycosyl hydrolases contain positively charged patches that are thought to play a role in membrane adherence and substrate binding. 28,29 On the other hand, some bacterial chitinases seem to exhibit rather high levels of surface hydrophobicity. In a previous study, it was noticed that the chitinase from Bacillus sp.…”
Section: Discussionmentioning
confidence: 98%
“…The presence of a cluster of positively charged residues in the catalytic domain of the chitinase B from Serratia marcescens was reported by van Aalten et al 27 Similarly, some other glycosyl hydrolases contain positively charged patches that are thought to play a role in membrane adherence and substrate binding. 28,29 On the other hand, some bacterial chitinases seem to exhibit rather high levels of surface hydrophobicity. In a previous study, it was noticed that the chitinase from Bacillus sp.…”
Section: Discussionmentioning
confidence: 98%
“…Among GH1 enzymes, Phob-gly has some peculiarities; it is monomeric, while the majority of the other members of the family is oligomeric, and the inspection of the 3D-structure suggested that it could be membrane-bound (Akiba et al 2004). In Scheme 1. addition, alkyl glucosides are good substrates of Phob-gly suggesting that the enzyme could be involved in the synthesis of glycolipids in vivo (Matsui et al 2000;Akiba et al 2004).…”
Section: Introductionmentioning
confidence: 97%
“…To date, the 3D structures of 18 GH1 β-glucosidases (in either resting, complexed, or transition state) have been determined from Eukaryota, [4][5][6][7][8][9][10][11][12] Bacteria [13][14][15][16][17][18] and Archaea. [19][20][21][22] Although the extent of sequence identity varies between 17% and 45% in the β-glucosidases, all the enzymes display a common (β/α) 8 -barrel motif. Apart from plant myrosinases and Klotho (KL) family members, all family 1 β-glucosidases conserve two catalytic glutamate residues located at the C-terminal end of β-strands 4 and 7.…”
Section: Introductionmentioning
confidence: 99%